Crater effects of shallow burial explosions in soil based on SPH-FEM analysis - Cui, Ying; Li, Zhangjian; Fang, Jun; Zhao, Ben (Frontiers in Earth Science, 2023)
By the design and implementation of static explosion experiment and numerical simulations, the effects and influencing factors of shallow buried explosions in soil were studied. Based on the static explosion test data obtained, the numerical analysis model of SPH-FEM was established, and the explosion process and pit parameters in shallow buried soil were also analyzed. By numerical calculation and comparison, the effectiveness of SPH-FEM method in simulating shallow buried explosion in soil was verified. Furthermore, the similarities and differences between the SPH-FEM method and the ALE method in the numerical simulation of the same explosion in the soil were discussed. The relationship between the radius of the blasting pit and the depth of the explosives buried, and the relationship between the weight of explosives and the volume of the pit were analyzed both. And the empirical curve formula of the depth of the explosives and the radius of the crater with the 9.35kg TNT explosive was obtained by mathematical fitting method. The results show that the SPH-FEM method was more refined and more computationally efficient than the ALE method to simulate shallow burial explosions in soil. The established empirical curve formula which expressed the relationship between the depth of explosive burial and the radius of the pit could effectively predict the radius of the pit of the shallow burial explosion. With the increase of the depth of the explosive burial, the radius of the pit increased to the peak value, and then the radius of the pit would decrease rapidly with the increase of the buried depth of the explosion.